2016
DOI: 10.1080/10520295.2016.1183820
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of irisin in skin, eye, and thyroid and pineal glands of the crested porcupine(Hystrix cristata)

Abstract: Irisin was first identified in muscle cells. We detected irisin immunoreactivity in various organs of the crested porcupine (Hystrix cristata). In the epidermis, irisin immunoreactivity was localized mainly in stratum basale, stratum spinosum and stratum granulosum layers; immunoreactivity was not observed in the stratum corneum. In the dermis, irisin was found in the external and internal root sheath, cortex and medulla of hair follicles, and in sebaceous glands. Irisin immunoreactivity was found in the neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In the study by Huh et al, FNDC5 expression was also identified in the thyroid, however, at a much lower level than in tissues containing muscle fibres . The thyroid gland of the crested porcupine (Hystrixcristata) has also been described to exhibit irisin immunoreactivity . As other metabolically active novel peptides, such as ghrelin, obestatin or visfatin, are influenced by thyroid hormones levels, this influence on irisin concentration has become an interesting focus of research.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Huh et al, FNDC5 expression was also identified in the thyroid, however, at a much lower level than in tissues containing muscle fibres . The thyroid gland of the crested porcupine (Hystrixcristata) has also been described to exhibit irisin immunoreactivity . As other metabolically active novel peptides, such as ghrelin, obestatin or visfatin, are influenced by thyroid hormones levels, this influence on irisin concentration has become an interesting focus of research.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, irisin immunoreactivity was found in the neural retina of the crested porcupine (Hystrix cristata). 20 To our knowledge, this is the only study showing that irisin exists in the human aqueous humor.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, the immunoreactivity of irisin was observed in the cornea ( 23 ). Another study of crested porcupine ( Hystrix cristata ) showed the immunoreactivity of irisin in the neural retina ( 24 ). Recently, two studies identified that irisin could be detected in the human aqueous humor and one study found that it could be detected in the vitreous humor ( 22 , 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%